Facilities audit for “surau” building in housing estates / Mirza Fariza Narawi - Narawi, Mirza Fariza (Faculty of Architecture, Planning and Surveying, 2008)
The responsibilities of public property management in Malaysia including “surau” building are distributed among various government departments and often managed in reactive manner. Improper supervision has lead to poor performance which was due to lack of property objectives. This dissertation focused on to determine the state and the condition of the facilities in “surau” building, to investigate the neighborhoods views about facilities provided, to identify the problem arise due to the facilities provided and to propose recommendation to improve the facilities in “surau” building. In order to achieve the objectives identified, literature review was done, then data was collected using questionnaires and observation also be done to identify the condition of the facilities provided. The collected data from the questionnaires was analyzed by using Microsoft Excel. Finding had shown that although many “surau” building have their own communities but the condition of the facilities provided still at average level. Besides that, some of the facilities that stated in the guidelines given by Majlis Bandaraya Shah Alam are not provided in the “surau” building. These problems occur because of improper maintenance practice and lack of supervision by Jabatan Agama Islam Selangor and Majlis Bandaraya Shah Alam. Hence, to improve the condition of the facilities provided in “surau” building, person who involved in “surau” building such as Jabatan Agama Islam, Majlis Bandaraya Shah Alam and the communities of the “surau” building need to take an immediate action to improve the condition of the facilities in their “surau” building and Jabatan Agama Islam should provide enough budget to them to make sure the facilities provided that stated in the guidelines will be provided in the “surau” building.